Розробка способу безперервного моніторингу опору рамного кріплення і його піддатливості - Захарова, Л.М.; Гріньов, В.Г.; Дєдіч, І.О.; Гордієнко, М.Е.; Кусень, А.Б.; Френтцель, Е.В.; Назимко, В.В. (Физико-технические проблемы горного производства, 2017)
Розроблено спосіб, який забезпечує можливість безперервного моніторингу піддатливості рамного кріплення та його опору гірському тиску протягом усього терміну експлуатації виробки. Розроблена конструкція пристрою для надійної реалізації способу та підібрані її раціональні параметри. Проведено аналіз результатів випробування нової технології й поставлені задачі подальших досліджень. Разработан способ, обеспечивающий возможность непрерывного мониторинга податливости рамной крепи и её сопротивления горному давлению в течение всего срока эксплуатации выработки. Разработана конструкция устройства для надежной реализации способа и подобраны ее рациональные параметры. Проведен анализ результатов испытания новой технологии и поставлены задачи дальнейших исследований. We developed a method providing continuous monitoring of frame support pliability and resistance to ground pressure during the term of its service. This method provides continuous and instantaneous monitoring of the pliability as well as frame of the support. The method spends no extra energy and drivers. This method has been implemented in practice owing a special design construction. The device is safe and reliable because pure mechanical approach was adopted during its development. Optimal parameters nave been chosen to provide reliable functioning of the gage. We described the results of the gage testing in laboratory conditions. A set of tasks were delineated that should be accomplished during further investigation.